Clinical Features of Patients With Acute Aortic Dissection After an Earthquake: Experience from the Kumamoto Earthquake 2016. (18th November 2019) - Komorita, Takashi; Fujisue, Koichiro; Sueta, Daisuke; Sakamoto, Kenji; Yamamoto, Eiichiro; Hashimoto, Yoichiro; Sakamoto, Tomohiro; Tsunoda, Ryusuke; Uesugi, Hideyuki; Suzuki, Ryusuke; Naito, Hisaki; Hanzawa, Kazuhiko; et al.
Abstract: BACKGROUND: While there is a concern about the increase in the occurrence of acute aortic dissection (AAD) caused by the worsening of hypertension, mental stress, etc., there is a lack of data regarding the influence of disasters on this event. The aim of this study was to address this issue in the acute–subacute phase after the Kumamoto Earthquake occurred on 14 April 2016. METHODS: We retrospectively investigated the impacts of the Kumamoto Earthquake on various cardiovascular diseases, including AAD, utilizing the medical records of patients in 16 hospitals in Kumamoto Prefecture during the period from 14 April to 30 June (78 days) in 2014, 2015, 2016, and 2017. RESULTS: The occurrence of heart failure and venous thromboembolism increased significantly in the acute–subacute phase after the earthquake. When comparing the earthquake year (2016) to the non-earthquake years (2014, 2015, and 2017), the difference in the occurrences and mortalities of AADs were not significant. When other characteristics of the patients were compared between the earthquake year and the non-earthquake years, there were no differences. CONCLUSIONS: It might be possible that the Kumamoto Earthquake did not affect the incidence of AAD or deaths from AAD, possibly because the climate was mild and the preventive efforts based on previous experience were successful. REGISTRATION: University Hospital Medical Information Network (UMIN)-CTR (http://www.umin.ac.jp/ctr/ ). IDENTIFIER: UMIN000023864. PUBLIC ACCESS INFORMATION: Opt-out materials were available at the following website: http://www.kumadai-junnai.com/home/wp-content/uploads/shinsai.pdf .